2022
DOI: 10.20473/ijosh.v11i1.2022.54-62
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Individual Characteristics and Hearing Complaints in Home Industry Workers

Abstract: Introduction: Home metal industry is an informal industry activity engaged in the manufacture of metal. The process of metal-making crates noise that causes hearing loss complaints in workers. The purpose of this study was to analyze the relationship between workers’ individual characteristics and hearing complaints in metal-making home industry workers in Ngingas North Village, Sidoarjo Regency. Methods: This research used an analytic observational method with a cross sectional design. The population was 28 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…Based on the analysis, respondents who did not use ear protection equipment were at risk for hearing disorders of 11,600 times compared to respondents who used it (OR=11,600; 95% CI=3,120). This research is also in line with research conducted on metalmaking workers in home industry which showed that there was a relationship between the use of ear protection and hearing complaints (Yudhistira et al, 2022).…”
Section: The Relationship Between Compliance With the Use Of Ear Prot...supporting
confidence: 88%
“…Based on the analysis, respondents who did not use ear protection equipment were at risk for hearing disorders of 11,600 times compared to respondents who used it (OR=11,600; 95% CI=3,120). This research is also in line with research conducted on metalmaking workers in home industry which showed that there was a relationship between the use of ear protection and hearing complaints (Yudhistira et al, 2022).…”
Section: The Relationship Between Compliance With the Use Of Ear Prot...supporting
confidence: 88%